Sense or sensibility? Exploring the motivations behind fandom nationalism expression in China - Lan, Jie; Waheed, Moniza; Bidin, Rosmiza (Elsevier B.V., 2026)
Organized fandom has become a defining feature of contemporary subculture, sociocultural dynamics, and even political discourse. In China, however, direct interaction between fan communities and the political sphere remains relatively limited, except in cases involving nationalist movements. The underlying motivations driving such fandom-based political participation remain insufficiently explored. In this study, 607 active fans with experience in fan communities were recruited to investigate the psychological and community-based mechanisms influencing fandom nationalism. Using partial least squares structural equation modeling, the results indicate that cognitive needs are significantly associated with fandom nationalism, whereas idol worship shows no direct effect. Contrary to prior assumptions that fan community engagement strongly mediates fans' political expression, this study found no significant mediating role of engagement. These findings contribute to deeper understanding of the motivational and structural dynamics underlying fans' political behavior in the context of digital China.